2004
DOI: 10.1097/00006231-200411000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Importance of receptor density in alpha radioimmunotherapy in B cell malignancies: an in-vitro study

Abstract: Binding assays confirm that SLVL samples present more CD20 antigens compared to B-CLL samples. Conventional therapies such as fludarabine, methylprednisolone or external gamma irradiation induce similar responses in the two populations but SLVL samples present higher sensitivity towards 213Bi-rituximab. These data are in favour of alpha-RIT in SLVL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In the current study, significant (P < 0.0001) induction of apoptosis as assessed by DNA fragmentation was observed after treatment with 213 Bi-hu3S193 and was most apparent following 72-h incubation. These results agree with several other studies assessing a-particle radioimmunotherapy in lymphoma and prostate cancers, where treatment was shown to induce cellular apoptosis (12,44). Phosphorylation of histone H2AX (g-H2AX) is known to occur in response to double-stranded DNA breaks and was assessed via immunoblotting (28).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the current study, significant (P < 0.0001) induction of apoptosis as assessed by DNA fragmentation was observed after treatment with 213 Bi-hu3S193 and was most apparent following 72-h incubation. These results agree with several other studies assessing a-particle radioimmunotherapy in lymphoma and prostate cancers, where treatment was shown to induce cellular apoptosis (12,44). Phosphorylation of histone H2AX (g-H2AX) is known to occur in response to double-stranded DNA breaks and was assessed via immunoblotting (28).…”
Section: Discussionsupporting
confidence: 90%
“…It is thought that high linear energy transfer radiation from a-emitter radiation results in irreparable double-stranded DNA breaks and severe chromosomal damage leading to the rapid and irreversible induction of apoptosis and cell death (8,12,43). In the current study, significant (P < 0.0001) induction of apoptosis as assessed by DNA fragmentation was observed after treatment with 213 Bi-hu3S193 and was most apparent following 72-h incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the successful use of high-LET a-emitters for targeted radionuclide therapy, suggesting their superiority over low-LET h-emitters in the treatment of solid tumors (21,22). In this study, we aim to evaluate the quantitative radiolabeling methods, stability, biodistribution, safety, and therapeutic efficacy of 213 Bi labeled to DOTATOC in the treatment of somatostatin receptor -expressing pancreatic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in line with previously published studies. Vandenbulcke [ 28 ] could show that [Bi-213]anti-CD20 induced significantly higher cell death rates in cells to which the antibody had a higher binding capacity. In a second study [ 27 ], they demonstrated that [Bi-213]anti-CD20 killed chronic lymphatic leukaemia cells more effectively than external gamma-irradiation underlining the importance of this novel therapeutic approach [ 27 ].…”
Section: Discussionmentioning
confidence: 99%